HUKUMAN DAN IMPLIKASINYA TERHADAP PEMBENTUKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN - Ummi Sa’adah (Nurul Jadid University, 2017)
This research is motivated by pesantren phenomenon known as educational institution which use punishment as a method to educate students. One of the pesantren that apply the penalty for improving discipline students is Pesantren Nurul Jadid Paiton Probolinggo. The focus of this research is the application of punishment and its impact on the discipline of santri. This research uses qualitative approach of case study type. The results showed that: 1) Planning of punishment program is done through recruitment, education and training and mentoring to pesantren board. 2) The punishment program is adjusted for the severity of the violation committed by the students. 3) Evaluation of punishment program is done through; direct and indirect supervision, coordination with central security.